CRISPR/Cas9-mediated targeted mutation of the E1 decreases photoperiod sensitivity, alters stem growth habits, and decreases branch number in soybean - Wan, Zhao; Liu, Yingxiang; Guo, Dandan; Fan, Rong; Liu, Yang; Xu, Kun; Zhu, Jinlong; Quan, Le; Lu, Wentian; Bai, Xi; Zhai, Hong (Frontiers in Plant Science, 2022)
The distribution of elite soybean (Glycine max) cultivars is limited due to their highly sensitive to photoperiod, which affects the flowering time and plant architecture. The recent emergence of CRISPR/Cas9 technology has uncovered new opportunities for genetic manipulation of soybean. The major maturity gene E1 of soybean plays a critical role in soybean photoperiod response. Here, we performed CRISPR/Cas9-mediated targeted mutation of E1 gene in soybean cultivar Tianlong1 carrying the dominant E1 to investigate its precise function in photoperiod regulation, especially in plant architecture regulation. Four types of mutations in the E1 coding region were generated. No off-target effects were observed, and homozygous trans-clean mutants without T-DNA were obtained. The photoperiod sensitivity of e1 mutants decreased relative to the wild type plants; however, e1 mutants still responded to photoperiod. Further analysis revealed that the homologs of E1, E1-La, and E1-Lb, were up-regulated in the e1 mutants, indicating a genetic compensation response of E1 and its homologs. The e1 mutants exhibited significant changes in the architecture, including initiation of terminal flowering, formation of determinate stems, and decreased branch numbers. To identify E1-regulated genes related to plant architecture, transcriptome deep sequencing (RNA-seq) was used to compare the gene expression profiles in the stem tip of the wild-type soybean cultivar and the e1 mutants. The expression of shoot identity gene Dt1 was significantly decreased, while Dt2 was significantly upregulated. Also, a set of MADS-box genes was up-regulated in the stem tip of e1 mutants which might contribute to the determinate stem growth habit.